A High-Density 45 nm SRAM Using Small-Signal Non-Strobed Regenerative Sensing - Verma, N.; Chandrakasan, A.P. (IEEE journal of solid-state circuits, 2009)
High-density SRAMs utilize aggressively small bit-cells, which are subject to extreme variability, degrading their read SNM and read-current. Additionally, array performance is also limited by sense-amplifier offset and strobe-timing uncertainty. This paper, presents a sense-amplifier that targets all of these performance degradations: specifically, simple offset compensation reduces sensitivity to variation while imposing minimal loading on high-speed nodes; stable internal voltage references serve as an internal means to self-trigger regeneration to avoid tracking mismatch in an external strobe-path; precise small-signal detection withstands small read-currents so that other bit-cell parameters can be optimized; and single-ended sensing provides compatibility to asymmetric bit-cells, which can have improved operating margins. The design is integrated with a 64-kb high-density array composed of 0.25 mum 2 6T bit-cells. A prototype, in low-power 45 nm CMOS, compares its performance with a conventional sense-amplifier, demonstrating an improvement of 4X in access-time sigma and 34% in overall worst case access time.